MIRERC 038/2025: EFFECTIVE USE OF ELECTRONIC HEALTH RECORDS IN TUBERCULOSIS SURVEILLANCE: A SURVEY OF TIGANIA EAST SUB-COUNTY, MERU COUNTY, KENYA - MERCY TONUI, CHEPKOECH; Dr. Patrick Kinyua Kubai, PhD; Dr. Amos Chege Kirongo, PhD, (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
no